2021
DOI: 10.1002/srin.202100226
|View full text |Cite
|
Sign up to set email alerts
|

3D Growth of Intragranular Pearlite in an Aged 100Mn13 Steel

Abstract: The morphology and microstructure of intragranular pearlite in 100Mn13 high‐carbon, high‐manganese steel aged at 600 °C are observed by a scanning electron microscope (SEM) and transmission electron microscope (TEM) and analyzed, and growth models describing the morphology and growth process in 3D space are proposed. The results show that pearlite could nucleate directly in the austenite grain and present a 3D morphology after deep etching, and ferrite and cementite in pearlite keep the orientation relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Figure 7e shows a phase transition zone between α-Fe and VC, where the ordered arrangement of VC gradually transitions to the ordered arrangement of α-Fe, with VC atoms gradually adjusting their positions to grow in the direction of α-Fe. Liang et al [20] also observed a similar phenomenon in ferritic steel. Based on the Bramfitt two-dimensional misfit degree theory [39] (Equation ( 1)), a two-dimensional misfit degree model for α-Fe and VC was constructed (as shown in Figure 7f), and the misfit degree (δ) between α-Fe and VC was calculated.…”
Section: Precipitatementioning
confidence: 64%
See 1 more Smart Citation
“…Figure 7e shows a phase transition zone between α-Fe and VC, where the ordered arrangement of VC gradually transitions to the ordered arrangement of α-Fe, with VC atoms gradually adjusting their positions to grow in the direction of α-Fe. Liang et al [20] also observed a similar phenomenon in ferritic steel. Based on the Bramfitt two-dimensional misfit degree theory [39] (Equation ( 1)), a two-dimensional misfit degree model for α-Fe and VC was constructed (as shown in Figure 7f), and the misfit degree (δ) between α-Fe and VC was calculated.…”
Section: Precipitatementioning
confidence: 64%
“…The nano-precipitation of VC can pin the slip of dislocations during deformation, thus increasing the strength of the material [ 19 ]. When precipitates form at austenitic grain boundaries, they can also serve as nucleation sites for pearlite growth [ 20 ]. The precipitation behavior of VC is related to the phase transformation temperature, aging time, and cooling rate [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%